2005
DOI: 10.1080/08910600510037217
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of saprophytic and water quality bacteria along the coast of the Aqaba and Suez Gulfs and Red Sea, Egypt

Abstract: Spatial and temporal variability of saprophytic (SB) and salt-tolerant saprophytic (STSB) bacterial counts as well total coliforms (TC), Escherichia coli (EC) and faecal streptococci (FS) were investigated in the Egyptian surface coastal waters of the Aqaba and Suez Gulfs as well as the Red Sea. A total of 200 samples was collected from 40 sites during January, March, May, July and September 2002. Hydrographical parameters including water temperature (8C), salinity (S ), dissolved oxygen (DO) and pH were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In 2011, TC, EC, and FS in water samples were used as indicators of microbial pollution. This study reported that the Suez Gulf is the most polluted among 194 sites in the Red Sea and Gulf of Aqaba (El-Shenawy and Farag, 2005; Ibrahim et al, 2011). …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In 2011, TC, EC, and FS in water samples were used as indicators of microbial pollution. This study reported that the Suez Gulf is the most polluted among 194 sites in the Red Sea and Gulf of Aqaba (El-Shenawy and Farag, 2005; Ibrahim et al, 2011). …”
Section: Introductionmentioning
confidence: 89%
“…Two studies have addressed human pathogens along the Red Sea coast (El-Shenawy and Farag, 2005; Ibrahim et al, 2011). In one study, the researchers measured the abundance of saprophytic (SB), salt-tolerant saprophytic (STSB), total coliforms (TC), Escherichia coli (EC) and fecal streptococci (FS) in 40 sites along the Egyptian Red Sea coastal waters and in the Aqaba and Suez Gulfs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different anthropogenic activities included recreational resorts, urban agglomeration, marine shipping, activities of phosphate industry and fishing ports, as well as limited freshwater and sewage sources. 2,20 The present study was conducted in order to monitor, investigate and Ecological Risk Assessment the accumulation of heavy metals (Cu, Cd, Zn, Ni and Pb) in coastal sediments in the intertidal zones between Al-Haymah and Al-Mokha of south Red Sea Coast Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…The Red Sea environments receive either locally or more widely, a variety of stresses as a result of human activities. The different anthropogenic activities included recreational resorts, urban agglomeration, marine shipping, activities of phosphate industry and fishing ports, as well as limited freshwater and sewage sources [2,19].…”
Section: Introductionmentioning
confidence: 99%